THE CONCEPT OF SYIRKAH AND ITS IMPLEMENTATION IN ISLAMIC FINANCIAL INSTITUTIONS - Sauqi, Muhammad Sauqi (JURNAL EKONOMI DAN BISNIS (EKOBIS-DA), 2024)
The concept of syirkah in Islamic economics plays a vital role as a form of partnership in various business fields, with the equitable distribution of capital, profit, and risk based on mutual agreement. This article discusses the definition of syirkah both etymologically and terminologically, referring to a partnership contract between two or more parties to run a joint business venture. The legal foundation of syirkah is explained through verses from the Qur'an, Hadith, and the consensus of scholars, demonstrating the significance of this concept in establishing an economic system based on fairness and transparency. This article also examines the pillars and conditions that must be met in executing syirkah as well as various types of syirkah, including syirkah milk and syirkah uqud. Additionally, the practice of syirkah in Islamic financial institutions, such as project financing through musyarakah contracts, is discussed in detail, illustrating its application in the modern world. Therefore, this article aims to provide a deeper understanding of the importance of syirkah as an instrument supporting sustainable economic development in accordance with Islamic principles